2000
DOI: 10.1002/1097-0215(20001120)89:6<494::aid-ijc5>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear morphometry in male breast carcinoma: Association with cell proliferative activity, oncogene expression, DNA content and prognosis

Abstract: To investigate the prognostic value of nuclear morphometry in male breast carcinoma (MBC), histological samples from 50 patients (mean age 62.2 years) were retrospectively analyzed by computerized nuclear morphometry. All patients received surgery; 35 had multiple combinations of adjuvant therapies. Mean follow‐up was 67 months (range 1–230). In each case, 100 tumor cells were measured, and the mean nuclear area (MNA), standard deviation of the nuclear area (SDNA), mean nuclear perimeter (MNP), standard deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…The differences also include nuclear features, like greater variations in nuclear sizes and shapes of Nigerian tumours. Nuclear morphometric parameters can identify an aggressive tumour phenotype and provide additional prognostic information for patients with invasive breast cancer (Chiusa et al, 2000;Tahlan et al, 2000;Jalava et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The differences also include nuclear features, like greater variations in nuclear sizes and shapes of Nigerian tumours. Nuclear morphometric parameters can identify an aggressive tumour phenotype and provide additional prognostic information for patients with invasive breast cancer (Chiusa et al, 2000;Tahlan et al, 2000;Jalava et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…These features are quite common among MBC, 25 but in striking contrast with the papillary pattern and the bland nuclear features of the present case. In fact, DNA ploidy, 5cER and 2cDI values are generally in line with cytological grading, 14,[25][26][27] and besides aneuploidy, c-erbB-2 overexpression and high Ki-67 values are also considered unfavorable prognostic parameters. [25][26][27] This is an important point because, although classic PC is generally treated with surgery and tamoxifen, in this case the described features warranted adjuvant chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…These results are in agreement with multiple studies that have shown the prognostic significance of nuclear morphometry in female and male breast cancer patients. [2][3][4][5][6][7][8] Altogether, this suggest that prognostication in male breast cancer could benefit from replacing classical nuclear atypia scoring according to the Bloom and Richardson grading system by automated nuclear morphometry of whole slide images.…”
Section: Discussionmentioning
confidence: 98%
“…The usefulness of nuclear morphometry by image analysis in providing more objective and reproducible prognosis for breast cancer patients has been recognized for a long time. [2][3][4][5][6][7][8] Prognostically important features express the nuclear size and shape (and in some cases the nuclear texture and the architecture of the tissue 9 ) in a quantitative manner. Incorporating nuclear morphometry features into grading would therefore make sense, but wider acceptance of such an approach to histological grading has been hampered by the tedious and time consuming nature of the manual segmentation of nuclei.…”
mentioning
confidence: 99%
See 1 more Smart Citation